2023
DOI: 10.1159/000531578
|View full text |Cite
|
Sign up to set email alerts
|

Arbeitsgemeinschaft Gynäkologische Onkologie Recommendations for the Diagnosis and Treatment of Patients with Early Breast Cancer: Update 2023

Abstract: Background: Each year the interdisciplinary AGO (Arbeitsgemeinschaft Gynäkologische Onkologie, German Gynecological Oncology Group) Breast Committee on Diagnosis and Treatment of Breast Cancer provides updated state-of-the-art recommendations for early and metastatic breast cancer. Summary: The updated evidence-based treatment recommendation for early and metastatic breast cancer have been released in March 2023. Key messages: This paper concisely captures the updated recommendations for early breast cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 109 publications
0
20
0
2
Order By: Relevance
“…In patients who have endocrine therapy, these numbers decreased to 62 and 40%, respectively. In the German guidelines [ 3 , 6 ], individual discussion of adjuvant radiotherapy with consideration of the individual risk profile is recommended. Endocrine therapy is not universally recommended in the German guidelines.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In patients who have endocrine therapy, these numbers decreased to 62 and 40%, respectively. In the German guidelines [ 3 , 6 ], individual discussion of adjuvant radiotherapy with consideration of the individual risk profile is recommended. Endocrine therapy is not universally recommended in the German guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the numerous randomized controlled trials for invasive breast cancer, the BIG 3–07/TROG 07.01 trial showed similar outcomes among 503 patients randomized to conventional fractionation vs. moderate hypofractionation [ 8 ]. The AGO guideline includes moderate hypofractionation for DCIS with the same grade of recommendation as conventional fractionation (LoE 1a, GR A, AGO +) [ 6 ]. Although there is less evidence regarding moderate hypofractionation for DCIS than for invasive breast cancer, German experts agree that reduced acute toxicity, increased patient convenience, and decreased costs favor the use of moderate hypofractionation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations